Efficacy and safety of inhaled ambroxol hydrochloride solution in patients with lower respiratory tract infectious diseases: a randomized, double-blind, placebo-controlled, multicentre clinical trial - Di Wu; Xiuhua Fu; Faguang Jin; Hui Li; Zhiqiang Qin; Haoyan Wang; Hongmei Yue; Jie Zhang; Zhaolong Cao (BMC Infectious Diseases)
Abstract Background Ambroxol is a widely used mucoactive agent, but the efficacy of inhaled ambroxol in patients with lower respiratory tract infectious (LRTI) disease is poorly understood. This trial aimed to compare the efficacy and safety of inhaled ambroxol with those of placebo in patients with LRTI diseases. Methods In this randomized, double-blind, placebo-controlled, multicentre clinical trial, 240 patients with LRTI diseases were randomized to receive inhaled ambroxol hydrochloride solution (ambroxol group, N = 120) or placebo (placebo group, N = 120) twice daily for 7 days. Results Compared with the placebo group, the ambroxol group had lower sputum trait scores and greater changes in sputum trait scores from Day 2 to Day 8. Compared with the placebo group, the ambroxol group presented lower expectoration difficulty scores and greater changes in expectoration difficulty scores on Days 2, 3, and 6. The sputum volume scores on Days 6, 7, and 8 were lower in the ambroxol group than in the placebo group, but the change in the sputum volume score was not different between the groups. Compared with the placebo group, the ambroxol group had lower cough scores on Days 3, 5, 6, and 7, as well as greater changes in cough scores on Days 2, 3, and 5. The incidences of adverse events (10.8% versus 6.7%), serious adverse events (0.8% versus 0.0%), and adverse reactions (4.2% versus 3.3%) were not different between the ambroxol group and the placebo group. Conclusions Inhaled ambroxol is better at ameliorating respiratory symptoms and has comparable safety to placebo in patients with LRTI diseases.